Is God ’n Verbondsgod? - J. L. Helberg (In die Skriflig, 1996)
In an article "Covenant Overload in Reformed Theology" John Stek (1994) reasons that in Reformed theology the concept covenant has been abstracted and separated from the narrative (and historical) specificity of the biblical covenants and has become a theological "concept" utilized to "construe" the “nature" of the God-humanity relationship. This article ties in with Stek showing that God is neither called Covenant God nor described as such in the Old Testament. The unique character of the covenant(s) of God is also pointed out and it is concluded that the being of God neither solely implies God's covenant with his people nor the expansion of his kingdom.